ANALISIS BAURAN PEMASARAN POLIKLINIK EKSEKUTIF RUMAH SAKIT DR.HASRI AINUN HABIBIE BERDASARKAN PROFESI - Alifia Ayu Delima (Bussman Journal : Indonesian Journal of Business and Management, 2022)
The marketing mix is ??marketing activities carried out in an integrated manner, which is carried out simultaneously among the elements in the marketing mix itself. According to Lovelock and Wright, in service marketing, the 4P instruments developed into 7Ps, namely product, price, place, promotion, people, process, and physical evidence. The executive polyclinic is one of the hospital's marketing strategies to achieve profit and existence in the community. There are many factors that influence consumer buying behavior, one of which is a personal factor, namely one's profession. The purpose of this study was to analyze the marketing mix of the executive polyclinic of Dr. Hasri Ainun Habibie Parepare Hospital based on profession. The method used is analytic observational with a cross sectional approach. The MANOVA test was conducted to see differences in demographic characteristics in influencing the dimensions of the marketing mix. The results of this study indicate that the responses of respondents by profession differ significantly in the dimensions of product, price, place, promotion, process, and physical evidence